Innovative work behavior: Role of organizational climate and employee creativity - Salsabila, Zana Hanan; Mansyur, Anwar (Universitas Ahmad Dahlan, 2024)
For companies, employees play an important role in bringing innovation to life. In improving employees innovative work behavior, researchers formulate factors such as organizational climate and employee creativity. This research uses quantitative techniques, with the object of research being one of the Internet Service Provider companies in Semarang. The sample in this study is 100 respondents who are employees of the company. This research analysis uses the Structural Equation Model approach using path analysis techniques on Smart PLS. The research results show that organizational climate positively and significantly affects innovative work behavior. Employee creativity has a positive and significant effect on innovative work behavior. Organizational climate has a positive and significant effect on employee creativity. Thus, to compete with Internet Service Provider companies, the organizational climate must be maintained, and employee creativity must be increased to create innovative work behavior within the company.